2021
DOI: 10.4103/tmj.tmj_199_20
|View full text |Cite
|
Sign up to set email alerts
|

Corneal topography and wavefront data changes in dry eye

Abstract: Background Dry eye is a very common eye presentation nowadays due to extensive use of digital devices, so that it was important for us to see the impact of dry eye on corneal topography and wavefront data because it has a strong relation with refractive surgeries. In the past, it was hard to know the effect of dry eye on corneal parameters, but after the new medical technology, it is possible to do that. Aim The aim of the study was to evaluate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…(7,20) In a prospective study, Montés-Micó et al (20) reported that the optical quality of the human eye is dynamic and is affected by the tear film. Kasem et al (21) showed a 1 to 5μm increase in peak central corneal thickness following treatment for DED. This was consistent with the findings of other studies that also reported a dramatic increase in peak central corneal thickness.…”
Section: Considerations Regarding the Measurement Of The Ocular Surfa...mentioning
confidence: 99%
“…(7,20) In a prospective study, Montés-Micó et al (20) reported that the optical quality of the human eye is dynamic and is affected by the tear film. Kasem et al (21) showed a 1 to 5μm increase in peak central corneal thickness following treatment for DED. This was consistent with the findings of other studies that also reported a dramatic increase in peak central corneal thickness.…”
Section: Considerations Regarding the Measurement Of The Ocular Surfa...mentioning
confidence: 99%